2021
DOI: 10.1089/hs.2020.0202
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation About COVID-19 in Sub-Saharan Africa: Evidence from a Cross-Sectional Survey

Abstract: Misinformation about coronavirus disease 2019 (COVID-19) is a significant threat to global public health because it can inadvertently exacerbate public health challenges by promoting spread of the disease. This study used a convenience sampling technique to examine factors associated with misinformation about COVID-19 in sub-Saharan Africa using an online cross-sectional survey. A link to the online self-administered questionnaire was distributed to 1,969 participants through social media platforms and the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 35 publications
(42 reference statements)
1
46
0
2
Order By: Relevance
“…Even health authorities have issued erroneous information (without scientific basis) about this compound in different media. While some of this information may be harmless, another portion may be dangerous and may affect the development and implementation of possible treatments (Osuagwu et al 2021), such as this compound. Our results show that CDS in the used dosage is safe and does not have severe side effects, even if used in higher doses (none of the non-success cases reported secondary effects after dose increase).…”
Section: Discussionmentioning
confidence: 99%
“…Even health authorities have issued erroneous information (without scientific basis) about this compound in different media. While some of this information may be harmless, another portion may be dangerous and may affect the development and implementation of possible treatments (Osuagwu et al 2021), such as this compound. Our results show that CDS in the used dosage is safe and does not have severe side effects, even if used in higher doses (none of the non-success cases reported secondary effects after dose increase).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional survey among 1969 respondents conducted in different African countries (Kenya, Cameroon, Ghana, Tanzania, Nigeria, South Africa, and Uganda), the study revealed that about 19% believed that the pandemic was designed to reduce world’s population, 22% thought the ability to seize your breath for ten seconds meant that you do not have COVID-19, 28% believed coronavirus can be washed down by drinking hot water, and 14% thought that COVID-19 had minimal effect on Blacks in contrast to Whites.” 88 The infodemic continues to undermine COVID-19 RCCE in many African countries which is further worsened by social media. 88 Some people still doubt the existence and nature of the outbreak and ignore safety precautions.…”
Section: Methodsmentioning
confidence: 99%
“…In a cross-sectional survey among 1969 respondents conducted in different African countries (Kenya, Cameroon, Ghana, Tanzania, Nigeria, South Africa, and Uganda), the study revealed that about 19% believed that the pandemic was designed to reduce world’s population, 22% thought the ability to seize your breath for ten seconds meant that you do not have COVID-19, 28% believed coronavirus can be washed down by drinking hot water, and 14% thought that COVID-19 had minimal effect on Blacks in contrast to Whites.” 88 The infodemic continues to undermine COVID-19 RCCE in many African countries which is further worsened by social media. 88 Some people still doubt the existence and nature of the outbreak and ignore safety precautions. 89 Some of the myths, rumors and misinformation reported in Zambia, Nigeria and some African countries include “The COVID reports are fabricated”, “It’s a strategy to get rid of Africans”, “Young people are immune to the pandemic”, “Communities without soap say maybe they can use very hot water for washing hands”, “People say masks are not meant for them but for a particular class of people and race”, “COVID-19 is cured by drinking ginger tea”, “It is a disease of the politicians”, “The people involved are just doing it for money’s sake”, “COVID is for the rich”, and “God is annoyed with humans because they have abandoned Him by stopping to gather for worship” among others.…”
Section: Methodsmentioning
confidence: 99%
“…Using an online survey (April–May 2020), it showed that false beliefs were shared by between 15% and 30% of the respondents, depending on the false statement assessed, with a higher likelihood of false beliefs in older and unemployed respondents. 13 In addition, three studies assessed COVID-19-related knowledge, attitudes and practices in Nigeria, in Ghana/South Africa and in the Republic of Chad (April–May 2020, March–April 2020 and May–August 2020, respectively) using online surveys. All three showed that study participants were very familiar with personal preventive measures against COVID-19 and the disease’s main symptoms.…”
Section: Introductionmentioning
confidence: 99%